Continuous Compaction Control (CCC) with Oscillating Rollers. (2016) - Pistrol, Johannes; Villwock, Sebastian; Völkel, Werner; Kopf, Fritz; Adam, Dietmar
Abstract: CCC systems are the state of the art method for an assessment of the achieved compaction success with vibratory rollers. However, CCC systems were not available for oscillatory rollers, which differ from vibratory rollers not only in their construction, but also in their motion behaviour and way of dynamically loading the soil. Experimental field tests were performed to analyse the motion behaviour of an oscillatory drum and a CCC value for oscillating rollers is presented based on empirical observations and a semi-analytical modelling of the drum-soil interaction. Moreover, the algorithm of the CCC value is tested on measurement data of the experimental field tests and the influence of weak spots on the CCC values is investigated.